Delays and underdiagnoses of dementia in the LMICs: Pathways and factors. (20th December 2022) - Ellajosyula, Ratnavalli; Narayanan, Jwala; Hegde, Soumya; Kamath, Vikram; Murgod, Uday; Easwaran, Vandana; Seetaram, Raghavendra; Srinivasan, Murali; Watson, Peter
Abstract: Background: Two thirds of people with dementia live in low and middle income countries (LMICs)but only about 10% of these persons are estimated to receive a dementia diagnosis. Reasons are multiple and complex. Early diagnosis is essential for initiating treatment, referral for care services, and planning for the future. There is a paucity of data on the pathways to dementia diagnosis in LMICs. We investigated the pathways and factors contributing to delay in diagnosis in a specialist memory clinic from urban India. Method: Consecutive patients and their carers attending the specialist memory clinic in Bangalore, India with cognitive complaints underwent a detailed clinical assessment, neuropsychological testing, neuroimaging, and blood tests. Details of symptom onset, visits to various medical providers, diagnoses made were captured on a proforma. Effect of education, gender, dementia subtype, and age of onset on time to diagnosis were examined using univariate analysis of covariance. Result: 879 out of 1212 patients had dementia. Only 24 (2.39%) received a dementia diagnosis elsewhere. Approximately 20% of the patients were on dementia‐specific medications but the family and the patient were unaware of the diagnosis. The median time to diagnosis was 24 (range 3 to 180) months. 43% of the patients were diagnosed 24 months after symptom onset. Patients with young onset dementia, Alzheimer's disease, and Frontotemporal dementia were diagnosed significantly later as compared to those with vascular dementia and dementia with Lewy bodies. Education and gender did not have an effect on the time to diagnosis. Conclusion: Both delay and lack of communication about the diagnosis of dementia appear to be important issues that need to be addressed to improve the early detection of dementia in India. Training of health providers appears an essential component in improving the early diagnosis of dementia. Findings from our study will be compared to literature from other LMICs and a comprehensive framework to improve early diagnosis of dementia in LMICs will be discussed.